1967
DOI: 10.1136/bmj.4.5576.391
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotrophic action of long-acting tetracosactrin compared with corticotrophin-gel

Abstract: Location of Placenta-Thompson et al. BMTM 391At the end of the scan the individual counting rates from each detector viewing the " hot" region indicate whether the placenta was anterior or posterior. ResultsThe indications for placentography were a suspicion of placenta praevia in 58 patients who presented with antepartum haemorrhage (52) or a persistent unstable lie at 37 weeks (6) (see Table), and the need to define the placenta before amniocentesis in four. The usual gestation period at which the test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
7

Year Published

1968
1968
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 14 publications
0
17
0
7
Order By: Relevance
“…Although the precise milligram depot-tetracosactide to International Units of ACTH relation is unclear, the best estimates are that 1 mg tetracosactide is equivalent to ∼80 U to 100 U ACTH gel in terms of maximal plasma cortisol concentration (20)(21)(22). However, depot-tetracosactide has a longer duration of action; mean plasma level had returned to normal by 24 h after the corticotropin gel, and by 48 h after I mg depot-tetracosactide.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Although the precise milligram depot-tetracosactide to International Units of ACTH relation is unclear, the best estimates are that 1 mg tetracosactide is equivalent to ∼80 U to 100 U ACTH gel in terms of maximal plasma cortisol concentration (20)(21)(22). However, depot-tetracosactide has a longer duration of action; mean plasma level had returned to normal by 24 h after the corticotropin gel, and by 48 h after I mg depot-tetracosactide.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Introduction Martinez-Manautou et al (1966, 1967 showed that continuous dosage with 0.5 mg. of chlormadinone acetate daily exerted an antifertility effect, though ovulation was not always inhibited. In a trial involving over 900 women for more than 8,000 cycles only one pregnancy occurred that could be attri-buted to a failure of the method, giving a pregnancy rate of 0.2 per 100 woman-years.…”
Section: Immentioning
confidence: 99%
“…It has potent corticotrophic properties but a length of action of only four to five hours when used in an unmodified form (Landon et al, 1964). In order to produce a therapeutically useful preparation tetracosactrin has been adsorbed on to zinc phosphate to delay its absorption from the site of injection (tetracosactrin depot, Synacthen depot, Cortrosyn depot) and the adrenocorticotrophic actions of this compound last for 24 to 48 hours after an intramuscular injection of 1 mg (Besser et al, 1967;Nelson et al, 1968;Haupt et al, 1969;Treadwell and Dennis, 1969). However, this preparation may produce painful local reactions if given subcutaneously or sometimes intramuscularly (Besser et al, 1967;Nelson et al, 1968;Treadwell and Dennis, 1969), and this seems to be due to the contained zinc complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce a therapeutically useful preparation tetracosactrin has been adsorbed on to zinc phosphate to delay its absorption from the site of injection (tetracosactrin depot, Synacthen depot, Cortrosyn depot) and the adrenocorticotrophic actions of this compound last for 24 to 48 hours after an intramuscular injection of 1 mg (Besser et al, 1967;Nelson et al, 1968;Haupt et al, 1969;Treadwell and Dennis, 1969). However, this preparation may produce painful local reactions if given subcutaneously or sometimes intramuscularly (Besser et al, 1967;Nelson et al, 1968;Treadwell and Dennis, 1969), and this seems to be due to the contained zinc complexes. Occasionally generalized allergic reactions after tetracosactrin depot occur though in general it can be used in patients who are hypersensitive to animal ACTH (El-Shaboury, 1968;Jensen and Sneddon, 1969).…”
Section: Introductionmentioning
confidence: 99%